The psycho-physiology of overtraining and athlete burnout in swimming - Lemyre, N. (Biomechanics and Medicine in Swimming XI, 2010)
Understanding swimmers` response to training and competition continues to be a significant challenge. Although a great deal of research has previously attempted to better understand the psychological and physiological factors leading to maladaptive training responses in an elite swimmer population, very few attempted to integrate these two fundamental perspectives. Therefore, the aim of this study was to investigate the relationship between personal dispositions, contextual motivation factors, subjective performance satisfaction, hormonal variation and burnout in elite swimmers. 53 elite swimmers (F=21, M=32) participated in a protocol of 6x200m progressive intervals during morning (07.00-08.30) and afternoon (14.00-15.30) training sessions. Venous blood was drawn before and after each sets of intervals and was analyzed for adrenocorticotropic hormone (ACTH) and cortisol by radio immune assays. This protocol was used at three time points during the season, corresponding to the easy, very hard and peaking time periods of the swimming season. Questionnaires assessing psychological variables were used together with the two-bout exercise test at three time points during the season. Using hierarchical regression analysis, results indicated that variation in basal cortisol (15%), maladaptive perfectionism disposition (20%), perceived mastery motivational climate (12%) and subjective performance satisfaction explained together a total of 67% of the variance in athlete burnout at season`s end. Hormonal monitoring is costly and invasive, current findings support the initial use of psychological monitoring, while hormonal monitoring may be used as a second step to help athletes steer away from maladaptive training outcomes such as athlete burnout